Effect of γ-irradiation on the display parameters of a room temperature ferroelectric liquid crystal mixture. Issue 7 (28th May 2021) - Debnath, Asim; Goswami, Debarghya; Singha, Biplab Kumar; Haldar, Sripada; Mandal, Pradip Kumar
ABSTRACT: A room temperature ferroelectric liquid crystal (FLC) mixture has been studied by irradiating with γ-radiation from 60 Co source. Important display parameters such as dielectric permittivity, conductivity, spontaneous polarisation, optical tilt angle, rotational viscosity and switching time have been determined as a function of the irradiation dose. Study reveals that transition temperatures involving different phases and optical tilt angle decrease significantly, more at higher doses, which means irradiation decreases the order parameter in different phases. Conductivity increases twelve times probably due to the production of ions or impurities by radiolysis process. Irradiation also affects the dynamics of the molecules manifested by the change in critical frequencies of relaxation modes. Changes in other electro-optic properties suggest that degradation of display quality may not be significant at low γ-radiation exposure but the effect will be severe at high dose. Graphical abstract: